2012
DOI: 10.1515/hf.2011.167
|View full text |Cite
|
Sign up to set email alerts
|

Vibration method for grading of large cross-section coniferous timber species

Abstract: The non-destructive testing (NDT) of timber using the longitudinal vibration method is based on the natural frequency of wood which is in relation to its quality. In the present paper, the suitability of this tool is investigated and the results of grading 395 pieces are presented. Structural timber of Radiata pine ( Pinus radiata D. Don.), Scots pine ( Pinus sylvestris L.), and Laricio pine [ Pinus nigra ssp. salzmannii (Dunal) Franco] from Spanish sources were investigated. The specimens were tested for bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
4
17
1
1
Order By: Relevance
“…Later, the suitability of this tool was tested in a wider set of coniferous species [395 pieces of radiata pine, Scots pine, and Corsican pine (Pinus nigra subsp. laricio)] from Spanish sources, and the great potential for stress grading of coniferous timber was demonstrated in agreement with European Standard EN 14081-2 (2005) (Arriaga et al 2012). The quoted standard specifies requirements for initial-type testing of machine-graded structural timber and for strength grading machines.…”
Section: Introductionsupporting
confidence: 63%
“…Later, the suitability of this tool was tested in a wider set of coniferous species [395 pieces of radiata pine, Scots pine, and Corsican pine (Pinus nigra subsp. laricio)] from Spanish sources, and the great potential for stress grading of coniferous timber was demonstrated in agreement with European Standard EN 14081-2 (2005) (Arriaga et al 2012). The quoted standard specifies requirements for initial-type testing of machine-graded structural timber and for strength grading machines.…”
Section: Introductionsupporting
confidence: 63%
“…For the Young's modulus after drying, comparing the ρ a(o) V a(o) 2 , calculated from density and stress wave propagation velocity and the MOE a(o) , ρV 2 was larger than MOE by 8.3% at the measurement points of pith and by 13.9% at the mature wood, respectively. It is considered that this tendency, which was also observed in the previous study [16], is due to the frequency-dependent (time-dependent) influence of the Young's modulus caused by the viscoelasticity of the timber.…”
Section: Relationship Between Moisture Content and The Rate Of Changesupporting
confidence: 76%
“…The methods are helpful for rapid testing and grading in practice, especially for high priced logs. Arriaga et al (2012) also observed a strong relationship between MOD stat obtained from bending test and MOD dyn by NDT (longitudinal vibration method applied for three conifer species). Similar correlations were also found in timber grading tests performed in poplar wood samples by Casado et al (2012).…”
Section: Relation Among Dynamic Moe and Mechanical Propertiesmentioning
confidence: 67%
“…In the last decades, much attention was paid to the non-destructive evaluation of wood properties, especially with regard to mechanical grading. In this context, non-destructive (NDT) and semi-destructive techniques (SDT) can be differentiated for evaluating wood and woodbased materials, which are useful for the assessment of standing trees or in-place structures (Brashaw et al 2009;Biechele et al 2011;Arriaga et al 2012;Casado et al 2012). These techniques are reasonably good predictors of timber properties under field conditions and detection of decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation